The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1992
DOI: 10.1111/j.1439-0434.1992.tb01237.x
|View full text |Cite
|
Sign up to set email alerts
|

Colletotrichin Causes Rapid Membrane Damage to Plant Cells

Abstract: The effect of colletotrichin, purified from Colletotricbum tabacum, on a diverse array of physiological processes was determined. Colletotrichin caused rapid loss of membrane integrity, as measured by cellular electrolyte leakage, in leaf discs of tobacco, cucumber, and four nightshade (Solanum) species floated on a 0.3 mM solution of the phy to toxin. The first ultrastructural damage observable was plasmolysis and disruption of the plasmalemma. Loss of membrane integrity occurred at similar rates in light or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…While some phytotoxins, e.g., helminthosporin, are host-specific (Wheeler, 1975), all of the Colletotrichum phytotoxins reported are nonspecific (Sahni et al, 1974;Gohbara et al, 1978;Duke et al, 1992). This is corroborated by the present study in which the partially purified phytotoxin was lethal to two non-hosts, lettuce and tobacco.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…While some phytotoxins, e.g., helminthosporin, are host-specific (Wheeler, 1975), all of the Colletotrichum phytotoxins reported are nonspecific (Sahni et al, 1974;Gohbara et al, 1978;Duke et al, 1992). This is corroborated by the present study in which the partially purified phytotoxin was lethal to two non-hosts, lettuce and tobacco.…”
Section: Discussionsupporting
confidence: 91%
“…The development of necrotic spots following inoculation of mango leaves with partially purified phytotoxin is similar to the effect of colletotrichins on tobacco leaves (Duke et al, 1992). Inhibition of seed germination is also a useful bioassay for demonstrating phytotoxicity (Gohbara et al, 1978;Yoder, 1980) and was confirmed by the lettuce and tobacco seed bioassays in our study.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Malathi et al (2002) also reported reduction of electrolytes loss caused by toxin produced from Collectrotricum falcatum, a sugarcane pathogen by its treatment with antagonists, P. fluorescens and T. harzianum. It has been observed that reduction of symptom production and electrolyte leakage by antagonists are positively correlated, which has been reported in various other crops such as oats by victorin (Damann et al 1974); and tobacco, cucumber and Solanum species by collectotrichin (Duke et al 1992). Our results were in agreement with Sriram et al (2000), who observed a sharp fall in electrolyte leakage after treating the pathotoxin from R. solani with the biocontrol agents.…”
Section: Discussionmentioning
confidence: 88%
“…En el filtrado del cultivo de Colletotrichum, se han encontrado sustancias fitotóxicas que interfieren con los mecanismos subcelulares y se sugiere que poseen actividad mutagénica (Jayasankar et al, 1998). También, se encuentran diversas enzimas que pueden degradar paredes celulares, macerar tejidos y alterar la permeabilidad de las células de la planta causando pérdida de la integridad foliar (Duke et al, 1992;Levi et al, 2007;Theerthagiri et al, 2008). Los metabolitos producidos por esta especie son de diferente tipo, entre ellos se encuentran; diterpenos como colletotricina A, B y C (Gohbara et al, 1978); taxol (Gangadevi, 2008); lpoliaminoacidos como las aspergillomarasmina A y B (Ballio et al, 1969) y pironas, como las colletopironas (Gohbara et al, 1976).…”
Section: Introductionunclassified